Is rotavirus gastroenteritis a more severe illness in patients of non-Irish ancestry?. (29th September 2015) - Nosherwan, A; Murphy, AM; Sasaki, E; Martin, C; Quinn, S; Harty, S; Roche, E; Hoey, H
Abstract : Introduction: Rotavirus is a leading cause of severe diarrhoea among young children. Worldwide more than 500 000 children under five die from rotavirus infection each year while almost 2 million require hospitalisation. No clear racial predilection has been demonstrated. WHO recommends that the rotavirus vaccine be included in national immunisation policies. In Ireland, rotaviral infection is common and in the local population classically causes a self-limiting illness of vomiting and diarrhoea lasting 2–3 days. The 2006 Government of Ireland census reported a 10% increase in our population since 2002, the majority of these being of non-Irish ancestry. The authors have noticed significant numbers of non-Irish and non-English speaking patients attending our paediatric services along with the impression that those inflicted with rotavirus tend to become more ill than anticipated. Aims: The aim of our study was to determine if paediatric patients in Ireland of non-Irish ancestry suffer a more protracted illness with rotavirus gastroenteritis than their Irish counterparts. Method: All patients who attended a paediatric hospital between 1 January 2007 and 31 December 2008 with a diagnosis of rotavirus gastroenteritis confirmed by electron microscopy on stool sample were identified from the hospital database. Their case notes were reviewed and the following information recorded: necessity of hospital admission, length of stay, level of dehydration, electrolyte abnormalities and other complications. Patients were segregated into two groups according to information obtained from their social history (Irish vs non-Irish ancestry) and the data from the groups compared. Results: During the 24-month study period, 286 patients met the inclusion criteria of whom 252 (88%) were of Irish and 34 (12%) of non-Irish ancestry. Hospitalisation was required in 85% (242) of cases (88% of the non-Irish and 84% of the Irish group). Moderate dehydration was seen in 44% (15) of the non-Irish and in 35% (89) of Irish group. Average length of stay in hospital for Irish patients and non-Irish patients was 2.3 and 3.08 days, respectively. No differences were seen with regard to electrolyte abnormalities or hypoglycaemia. No patient required admission to intensive care. There were no deaths. Conclusion: Children of both Irish and non-Irish ancestry exhibit significant morbidity when infected with rotavirus with the latter group suffering a more severe illness hence extra caution is required in their management. The rotavirus vaccine should be offered to the paediatric population in Ireland.